Project- Based Learning and Problem-Based Learning: Are They Effective to Improve Student’s Thinking Skills? (Jurnal Pendidikan IPA Indonesia, 2017)
The study aims at finding (1) the effect of project-based learning and problem-based learning on student’s creativity and critical thinking and (2) the difference effect of project-based learning and problem-based learning on student’s creativity and critical thinking. This study is quasi experiment using non-equivalent control-group design. Research population of this study was all classes in eleventh grade of mathematics and natural science program of SMA N 1 Temanggung. The participants were 102 students. This study used three classes as research sample which implemented three different kinds of learning models in respiratory system. XI MIPA 3 was as an experimental group implementing project- based learning and XI MIPA 5 was as an experimental group implementing problem- based learning, while XI MIPA 1 was as control group. Data was collected using two instruments to measure student’s creativity and student’s critical thinking. Data was analysed using t- test, multivariate analysis, and univariate analysis. The results reveal that (1) project-based learning and problem-based learning affect student’s creativity and critical thinking; (2) there is a difference effect of project-based learning and problem- based learning on student’s creativity; and (3) there is no difference effect of project-based learning and problem-based learning on student’s critical thinking.